2020
DOI: 10.1103/physreve.102.032302
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in outcomes of repeated instances of percolation experiments

Abstract: We investigate the heterogeneity of outcomes of repeated instances of percolation experiments in complex networks using a message passing approach to evaluate heterogeneous, node dependent probabilities of belonging to the giant or percolating cluster, i.e. the set of mutually connected nodes whose size scales linearly with the size of the system. We evaluate these both for large finite single instances, and for synthetic networks in the configuration model class in the thermodynamic limit. For the latter, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…3 and 4. Other prominent features seen in the heat maps are not captured by these families of curves, as they require an analysis of local environments of nodes and edges beyond first coordination shells, as discussed and exploited before in [24,33] to rationalize prominent features in pdfs of percolation probabilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 and 4. Other prominent features seen in the heat maps are not captured by these families of curves, as they require an analysis of local environments of nodes and edges beyond first coordination shells, as discussed and exploited before in [24,33] to rationalize prominent features in pdfs of percolation probabilities.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we demonstrated that the message passing approach to percolation -apart from its original purpose to compute heterogeneous node-dependent percolation probabilities [25,33] -can also be utilized to evaluate heterogeneous node dependent probabilities of vertices in a complex networks to be APs as well as het-erogeneous edge dependent probabilities of pairs of neighboring vertices in a network to be connected by a bredge.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By convention in statistics physics, we will resort to mean-field theory [2,23], which allows us to appreciate the average network structure characteristics in the large graph size limit. An orthogonal dimension to network robustness is the stability, which looks into the common nodes shared by a functional component such as giant component [31,32] and Gk-core [20] when a network undergoes repeated independent percolation processes. A higher number of common nodes indicates a stronger stability of the network as these nodes are likely to be retained regardless of a specific adverse event.…”
Section: Robustness and Stability Of Gk-coresmentioning
confidence: 99%